2000
DOI: 10.1046/j.1365-2699.2000.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Bird distribution in riparian vegetation in the extensive natural landscape of Australia’s tropical savanna: a broad‐scale survey and analysis of a distributional data base

Abstract: Aim (a) To characterize the riparian bird assemblage, and its variation, in a large area of northern Australia; (b) to examine the distinctiveness of this assemblage in relation to the broader landscape; (c) to consider the influence of disturbance on this assemblage; (d) to examine temporal variability in the riparian assemblage, and especially evidence for seasonal movements between riparian and non-riparian areas.Location c. 620,000 km 2 of the seasonal tropics of the Northern Territory, Australia.Methods (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 36 publications
6
61
0
2
Order By: Relevance
“…The relative abundance of food resources near tidal creeks may be one reason for high bird species richness in the mangroves (Figure 1). An increase in bird species richness in riparian zones compared to nonriparian zones was also observed in Australian savanna, due to the greater plant species richness and structural complexity of riparian zones [30].…”
Section: Conclusion and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The relative abundance of food resources near tidal creeks may be one reason for high bird species richness in the mangroves (Figure 1). An increase in bird species richness in riparian zones compared to nonriparian zones was also observed in Australian savanna, due to the greater plant species richness and structural complexity of riparian zones [30].…”
Section: Conclusion and Discussionmentioning
confidence: 72%
“…Besides being an important factor in contributing to the increase in species richness and diversity, habitat structure is also an important determinant influencing habitat selection and distribution of species, especially in complex habitats such as tropical forest [29]. For example, in the Northern Territory, Woinarski et al [30] reported that species richness and abundance of birds was significantly greater in forested riparian zones compared to non-riparian habitats, and that species composition also varied within habitats depending on their relative complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, riparian habitats are often cited as harboring higher numbers of species than adjacent upland habitats within the same geographic location (Naiman et al 1993, NRC 2002. This pattern has been observed in some systems (McIntyre 2000, Woinarski et al 2000, Catterall et al 2001, Brown and Peet 2003, but not in others (McComb et al 1993, Hughes and Cass 1997, Treonis et al 1999, Catterall et al 2001, Pearson and Manuwal 2001. In some systems, in fact, the opposite gradient (higher upland diversity) has stronger support (McGarigal and McComb 1992, Kirkman et al 1998, Burnham 2002, Schade et al 2003.…”
Section: Introductionmentioning
confidence: 87%
“…These highly fragmented environments now harbour much of the relictual biota of northern Australia and support biotic communities very different to the far more pervasive savanna woodlands (Specht 1958;Taylor and Dunlop 1985;Russell-Smith 1991;Russell-Smith et al 1992;Woinarski 1993Woinarski , 2004Woinarski et al 2000a).…”
Section: Australia's Tropical Savannasmentioning
confidence: 99%
“…Vegetation types that contrast with the tropical savanna matrix add a further mix of bird species to the regional pool, but because of the small extent and patchiness of these habitats, their bird species richness is generally low. This is particularly so for rainforests and riparian forests, whose bird communities are attenuated from higher to lower rainfall areas of northern Australia, and from east (Cape York Peninsula) to west (Kimberley) (Johnstone and Burbidge 1991;Woinarski 1993;Woinarski et al 2000a). A small number of bird species are closely associated with Melaleuca woodlands and forests (e.g.…”
Section: Birds and Bird Assemblages In Monsoonal Australiamentioning
confidence: 99%